(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2010)
This paper studies data mining as a nPw and emerging tool for Market Analysis. Thi:, reveals that Data Mining which is the process of extracting various kinds of business infonnation from the data warehouse helps in various f unctional areas of market analysis i.e. Market based analysis, customer profiling, web marketing ere. to gain the competitive advantage for the organization. Jr shows that Data Mining tools perform market analysis by clearing business data, enhancing customer knowledge, enhanced marketing strategies and increasing profits. This paper reveals how to gain compe//// ve edge and enhance business profitability and efficie11cy . Business organizations worldwide are taking help of different Data Mining tools. Data Mining fills the growing gap between large storage systems and powerful retrieval systems and ability to analyze the information obtained. It helps contribute to research by providing association techniques, techniques for on-line discovery, ensemble learning and distributed data sets. Large number of marketing analysis techniques are related to sales forecasting which can be performed by the data mining tools. It shows if tools are used by marketing managers effectively then it provides an edge to their business.